Teacher Creativity in Utilizing Learning Media for Fiqh Subjects at MI Al Mawaddah Warrahmah Kolaka - Suwarna, Sabri Deki; Zakariah, M. Askari; Zakariah, Abdul Haris Nasution (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to analyze teacher creativity in utilizing learning media in Fiqh subjects at MI Al Mawaddah Warrahmah Kolaka and identify supporting and inhibiting factors. This study is motivated by the importance of teacher creativity in using learning media to improve the effectiveness of the teaching and learning process, especially in Fiqh learning, which is often considered monotonous and less interesting for students. This study uses a qualitative approach with descriptive methods. Data collection techniques were carried out through observation, interviews, and documentation involving the principal, Fiqh teachers, and students as research subjects. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion. The results of the study indicate that teacher creativity in utilizing learning media has begun to be applied through the use of laptops, the internet, and presentation media in delivering Fiqh materials. However, the implementation is not optimal because there are still obstacles such as limited technological skills, a lack of variety in media use, and facilities and infrastructure that are not fully supportive. Supporting factors include the availability of technological facilities and school support, while inhibiting factors include limited teacher competence in using technology and a lack of learning innovation. Therefore, it is necessary to improve teacher competency and optimize the use of educational technology to improve the quality and meaningfulness of Fiqh learning.